2007
DOI: 10.1007/s00384-007-0273-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative staging of rectal carcinoma by endorectal ultrasound: is there a learning curve?

Abstract: ERUS is an accurate method for staging rectal cancer pre-operatively. Accurate assessment of tumour stage can be achieved immediately by an experienced radiologist without specific training in ERUS. Nodal staging accuracy tends to improve with experience but reaches a plateau after 30 cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 57 publications
3
29
0
5
Order By: Relevance
“…Badger et al compared several studies and reported a N-stage TRUS accuracy of 59-82%. 7,19 Further investigations in our hospital will also include N-staging as indications for TEM in literature seem to expand to even T2 and T3 lesions after preoperative chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Badger et al compared several studies and reported a N-stage TRUS accuracy of 59-82%. 7,19 Further investigations in our hospital will also include N-staging as indications for TEM in literature seem to expand to even T2 and T3 lesions after preoperative chemoradiotherapy.…”
Section: Discussionmentioning
confidence: 98%
“…Third, patients who have undergone radiation therapy, with resulting edema, inflammation, and necrosis, tend to be overstaged more often than patients who have not. 1,6,7,18 The only overstaged patient in our series had indeed been biopsied prior to TRUS.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Ultrasonographic criteria for distinguishing malignant from inflammatory lymph nodes are a source of controversy. The criteria of echogenicity and border characteristics are subjective, although at least one study has shown that as many as 72% of nodes with hypoechoic patterns are metastatic (70). Nodal size as a criterion to consider a node to be metastatic is a matter of debate.…”
Section: Discussionmentioning
confidence: 99%